Association between low serum testosterone level and severe asthma among elderly women - Kai Ryu; Yuma Fukutomi; Eiji Nakatani; Yosuke Kamide; Kiyoshi Sekiya; Takeo Ishikawa; Takanori Numata; Jun Araya; Kazuyoshi Kuwano; Masami Taniguchi; Hiroaki Masuzaki (Allergology International)
Background: Elderly asthma has distinct pathophysiologic and phenotypic characteristics compared with asthma in younger patients. However, a potential relationship between sex hormones and the severity of asthma remains unknown in the elderly population. The aim of the present study was to elucidate the relationship between the level of circulating free testosterone and severity of asthma among Japanese with elderly asthma. Methods: The level of free testosterone was measured using sera from elderly patients with asthma aged ≥60 years (n = 192), and its association with the severity of asthma was examined after stratification by sex. Results: Based on previous literature and our preliminary analysis showing that current oral corticosteroid (OCS) use might be a risk factor for a lower free testosterone level regardless of severity of asthma, analyzed patients were limited to those who were not currently using OCS (n = 164). Regarding elderly men who were not currently using OCS (n = 62), there was no significant association between free testosterone level and severity of asthma. However, in female counterparts (n = 102), a low free testosterone level was significantly associated with severe asthma even after adjustment for age (p for trend, 0.03). Conclusions: The present study showed a significant association between the serum free testosterone level and severity of asthma among elderly women who were not currently using OCS. Although the causal relationship is unclear, this finding may provide a clue to understand the sex difference in the mechanisms of severe asthma in elderly populations.